2012
DOI: 10.14742/ajet.838
|View full text |Cite
|
Sign up to set email alerts
|

Pedagogical approaches for ICT integration into primary school English and mathematics: A Singapore case study

Abstract: <span>This case study research attempts to examine the pedagogical approaches for the teaching of English and mathematics with information communication technology (ICT) in a primary school in Singapore. The study uses the learning </span><em>with</em><span> and learning </span><em>from</em><span> ICT framework in reporting and analysing how ICT has been used in the teaching of English and mathematics. This framework also looks into the level of production … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 22 publications
2
29
0
4
Order By: Relevance
“…Moreover, studies which focused on the integration of technology in Mathematics teaching and learning present divergent results. While some researches concede that the use of technology in Mathematics teaching and learning has not led to any discernible improvements (Goodison, 2002;Hourigan & O'Donoghue, 2007;Biagi & Loi, 2013), others have shown that the use of technology effectively enhance students' understanding and enjoyment of Mathematics (Miller & Glover, 2007;Tay, Lim, Lim & Koh, 2012). It is identified as a tool and important component to support visualization and interactive media that assist representation, reasoning, calculation construct, exploring, and solving problem (Curri, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, studies which focused on the integration of technology in Mathematics teaching and learning present divergent results. While some researches concede that the use of technology in Mathematics teaching and learning has not led to any discernible improvements (Goodison, 2002;Hourigan & O'Donoghue, 2007;Biagi & Loi, 2013), others have shown that the use of technology effectively enhance students' understanding and enjoyment of Mathematics (Miller & Glover, 2007;Tay, Lim, Lim & Koh, 2012). It is identified as a tool and important component to support visualization and interactive media that assist representation, reasoning, calculation construct, exploring, and solving problem (Curri, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have reported that teachers use ICT more in English instruction compared to mathematics. For instance, in Singapore, Tay, Lim, Lim, and Koh (2012) reported that teachers incorporated ICT differently and more frequently in English classes than in mathematics. In mathematics, ICT was for skills practice compared to English classes where students used ICT in knowledge construction.…”
Section: Ict Usementioning
confidence: 99%
“…Other pedagogical benefits of digital storytelling include promoting the development of critical media skills (Ohler, 2006), motivating learning that leads to improved academic performance (Sadik, 2008;Tay, Lim, Lim, & Koh, 2012;Yang & Wu, 2012), encouraging divergent thinking (Kim, Choi, Han, & So, 2012) as well as self-review and cooperative learning that enable students to value emotional realities and encompass holistic means of constructing new knowledge (Alterio, 2003;Nicholas & Starks, 2014). In addition, storytelling requires students to make sense of experiences by acknowledging and integrating cultural, contextual and emotional realities into the storytelling processes (Bishop & Glynn, 1999).…”
Section: Theoretical Framework Underpinning Researchmentioning
confidence: 99%